"He was brainwashed!" Criminal complicity and sentencing in France: interpreting a "crime committed under influence". Issue 1 (23rd December 2020) - Ballot, Mickael; Niang, Anta; Laurens, Stéphane; Testé, Benoit
Abstract : Purpose: This paper aims to examine whether being shown a testimony alleging that the perpetrator of a crime was influenced by an accomplice has an impact on the severity of the sentence given to this accomplice. Design/methodology/approach: A total of 119 participants read the summary of a case of armed robbery. Two experimental conditions were adopted: the presence of a testimony suggesting the accomplice's influence on the perpetrator in committing the crime (versus no testimony). The participants were then asked what sentence they would give the accomplice and what sentence they would have given the perpetrator of the crime, who had in fact already been sentenced. The participants rated items relating to the explanation for the crime (perception that the perpetrator had been manipulated by the presumed accomplice) and to the presumed accomplice's intent to commit the crime. Findings: The participants showed themselves to be harsher towards the presumed accomplice when they were shown the testimony about his influence, which reduced the disparity with the sentence they would have given to the perpetrator of the crime. Analyses of mediation show that the participants shown the testimony (as opposed to those who were not) were more likely to say that the presumed accomplice manipulated the perpetrator of the crime, leading them to be more likely to attribute to the accomplice the intent to commit the crime and to be harsher towards him. Originality/value: The results of this research are discussed with a focus on naïve interpretations of influence in the very specific context of legal adjudication.